The Qur'an seminar commentary: a collaborative study of 50 Qur'anic passages = Le Qur'an seminar : commentaire collaboratif de 50 passages coraniques - Azaiez, Mehdi (De Gruyter eBook-Paket Theologie, Religionswissenschaften, Judaistik, 2016)
The Qur'an Seminar Commentary is an unprecedented work of collaboration in the field of Qur'anic Studies, involving the insights of 25 scholars on 50 Qur'anic passages. These scholars represent a diverse range of disciplinary backgrounds and provide readers with unique insights into the latest trends of research in the Qur'an. This Commentary is a useful and illuminating reference work for students and scholars in the field of Qur'anic Studies.